Implementation of Ibn Miskawaih's Theory on Modern Education - Mutiara, Dennis; Fauzi, Ahmad (Program Studi Pendidikan IPS, 2024)
Technological developments and globalization require participation from all levels of society to follow the trend, including by using smartphones. Even though it provides an easy access to reach some informations, the negative impact is visible in student behavior in education environment. This research uses a literature review with a qualitative approach to understand and interpret related phenomenas. The finding is regarding Ibnu Miskawaih's ethical theory shows human character can be formed by managing the soul. Ibnu Miskawaih proposed the theory of al-Insan al-Kamil with three levels of soul: Al-Nafs al-Bahimiyah, Al-Nafs as-Sabu'iyah, and Al-Nafs an-Nathiqiyah. Character formation is carried out through a process of habituation, praise, threats and punishment. Some Efforts to developing character in education can be realized by combining several aspects of modern education, from humanist aspects to cybernetic aspects with the aim of remaining connected to the surrounding environment, because human education begins and ends in how to act.